Association between physical activity and short‐term physical function changes after hip fracture: An observational study. (11th September 2020) - Taylor, Nicholas F.; Peiris, Casey L.; Thompson, Anne L.; Prendergast, Luke A.; Harding, Katherine E.; Hau, Raphael; Shields, Nora
Abstract: Background and Purpose: To investigate whether physical activity levels are predictive of short‐term changes in physical function for people discharged to independent living in the community following withdrawal of rehabilitation services after hip fracture; and to describe short‐term recovery in physical activity, physical function, walking confidence, health‐related quality of life and walking participation. Methods: This prospective cohort study comprised 57 older adults (39 females, mean age 80.4, SD 8.4 years) living independently in the community after hip fracture. Accelerometer‐based physical activity, physical function (Functional Independence Measure [FIM], de Morton Mobility Index, Frenchay Activities Index and Participation in outdoor walking), walking confidence and health‐related quality of life were measured after discharge from rehabilitation services (baseline) and 12 weeks later. Multiple linear regression analyses determined the ability of physical activity (daily steps), walking self‐confidence, health‐related quality of life and demographic factors (age, sex and time since fracture) to predict Week 12 physical function using Week 0 physical function as a covariate. Results: Participants at baseline averaged 4439 daily steps which did not change 12 weeks later. There were small increases in all measures of physical function and walking confidence, but not health‐related quality of life. Increased walking self‐confidence was associated with an increase in FIM total, FIM mobility and de Morton Index scores. Physical activity did not predict change in measures of physical function. Conclusions: Walking confidence of adults discharged from rehabilitation services after hip fracture had a greater association with short‐term recovery of physical function than level of physical activity. Community‐dwelling adults continue to make small short‐term improvements in physical function and walking confidence after discharge home and withdrawal of rehabilitation services.